Electric vehicle technology explained - Larminie, James; Lowry, John, 1948- (Hoboken : John Wiley & Sons, 2012)
Fully updated throughout, Electric Vehicle Technology, Second Edition, is a complete guide to the principles, design and applications of electric vehicle technology. Including all the latest advances, it presents clear and comprehensive coverage of the major aspects of electric vehicle development and offers an engineering-based evaluation of electric motor scooters, cars, buses and trains. This new edition includes:important new chapters on types of electric vehicles, including pickup and linear motors, overall efficiencies and energy consumption, and power generation, particularly for zero ca.
3.11 Use of Batteries in Hybrid Vehicles3.11.1 Introduction; 3.11.2 IC/Battery Electric Hybrids; 3.11.3 Battery/Battery Electric Hybrids; 3.11.4 Combinations using Flywheels; 3.11.5 Complex Hybrids; 3.12 Battery Modelling; 3.12.1 The Purpose of Battery Modelling; 3.12.2 Battery Equivalent Circuit; 3.12.3 Modelling Battery Capacity; 3.12.4 Simulating a Battery at a Set Power; 3.12.5 Calculating the Peukert Coefficient; 3.12.6 Approximate Battery Sizing; 3.13 In Conclusion; References; Chapter 4 Electricity Supply; 4.1 Normal Existing Domestic and Industrial Electricity Supply.
4.2 Infrastructure Needed for Charging Electric Vehicles.
Includes bibliographical references.
Print version record.
Keywords: Electric vehicles -- Technological innovations; Electric vehicles -- Design and construction; Electric vehicles -- Design and construction; Electric vehicles -- Technological innovations; Engineering; TRANSPORTATION -- Automotive -- Antique & Classic; Electric vehicles -- Design and construction; Electric vehicles -- Technological innovations; Electronic books